Pembelajaran Discovery Learning di Sekolah Menengah Kejuruan: Apakah Dapat Meningkatkan Kompetensi Siswa? - Febrika Yogie Hermanto; Siti Rahayu Nugraheni; Mar’atus Sholikah (Edunusa: Journal of Economics and Business Education, 2021)
This research was conducted to identify the learning that was conducted by using discovery learning models in improving student competence. This research is a classroom action research using three stages, which are conducted to SMK Negeri 1 Yogyakarta Students, the Competency of Office Automation and Management Skills (OAMS). This research was conducted on ten-grade students in the Office Technology Subject, Basic Competence (KD) 3.5 and 3.6, totaling 63 students who were divided into two classes. The results of this study indicate that as many as 58 students scored above the minimum score, and 3 students scored the same as the minimum score. Furthermore, on the daily test scores of KD 3.6, 15 students scored below the minimum score. Based on the results, this study concludes that the discovery learning conducted on SMK Negeri 1 Yogyakarta students can improve student competence where most of the students score above the minimum score, 5 students get the high score of 90, 3 students get the minimum score, and no student gets the score below the minimum score. Future research should be able to explore discovery learning using other methods, making questionnaires for students, and increasing the number of respondents to show the study results on a broader scale and deeper discussion.